Cinematographic Analysis and Authorship of Nollywood Contemporary Films in Nigeria - Aondover, Perpetua Ogechi; N. Amadi, Richard; Whyte, Dike Harcourt (Budapest International Research and Critics University, 2025)
This paper examines the cinematographic techniques and directorial authorship in contemporary Nollywood films, exploring how visual storytelling, lighting, camera work, and editing define the industry’s unique cinematic language. The study also evaluates the influence of individual directors in shaping the artistic and narrative structure of Nigerian films. The study investigates key trends, challenges, and the evolution of Nollywood’s cinematic identity in the global film landscape. The paper argues that Nollywood, Nigeria’s prolific film industry, has grown into one of the largest film-producing sectors in the world. Initially characterized by low-budget productions and direct-to-video releases, contemporary Nollywood has embraced high production values, sophisticated storytelling, and technical advancements. The paper points out that the concept of the Nollywood auteur is defined by the unique styles and recurring themes observed in the works of certain directors. Some Nollywood directors have developed a signature style, often seen in their recurrent themes, cinematographic choices, and narrative structures. Directors such as Kunle Afolayan, Perpetua Ogechi, Kemi Adetiba, and Niyi Akinmolayan are known for their distinctive storytelling and technical finesse. Despite advancements, Nollywood still faces challenges such as limited funding, infrastructural deficits, and constraints in distribution networks. However, the rise of streaming platforms like Netflix and Amazon Prime Video provides new opportunities for global visibility and increased production standards. The paper concludes that the evolution of cinematographic techniques and the emergence of auteur directors have significantly shaped contemporary Nollywood films.